One- and two-dimensional structures based on gallium nitride - Fabris, Guilherme S.L. [UNESP]; Paskocimas, Carlos A.; Sambrano, Julio R. [UNESP]; Paupitz, Ricardo [UNESP] (Elsevier, 2021)
Physical and chemical properties of non-conventional 2D and tubular structures constructed with combinations of Ga/N atoms are proposed and theoretically investigated. The structures were constructed taking as templates the architecture of Porous Graphene and Graphenylene. Density Functional Theory (DFT), considering periodic conditions was used to determine mechanical and electronic properties. Their mechanical stability was confirmed by verification of their compliance with Born-Huang conditions. Young modulus was found to be within the range 146 GPa ​≤ ​Y ​≤ ​493 GPa, values quite lower than those found for graphene (Y ~ 1047.94 GPa). On the other hand, Poisson ratio for the 2d materials was found to be around 0.371. Electronic structure calculations reveal that this new class of materials are typically large band-gap semiconductors with gap openings going up to Eg ~ 6.0 eV. Their vibrational signatures were calculated in order to contribute to identify their presence in future experimental works.
Keywords: Density functional theory; Electronic structure; III-V compounds; Inorganic nanotubes; Raman